Perspectives from health-care providers and women about completing human papillomavirus (HPV) self-testing at home. Issue 10 (26th November 2017) - Katz, Mira L.; Zimmermann, Barret J.; Moore, Deborah; Paskett, Electra D.; Reiter, Paul L.
ABSTRACT: Cervical cancer (CC) incidence and mortality rates are increased, and CC screening rates are low among Appalachian Ohio women. Mailing human papillomavirus (HPV) self-tests to women to complete at home is a potential new strategy to engage women in CC screening. The authors aimed to gain insights into the perceived acceptability of mailed HPV self-tests. Focus groups were conducted (August 2014–January 2015) among providers (physicians, nurse practitioners, nurses) and women in Appalachian Ohio. Providers ( n = 28) and women ( n = 15; age range: 32–62 years) reported general acceptance of HPV self-tests, however, for different reasons. Providers thought HPV self-testing would increase the proportion of under-screened women returning to the health-care system, while women thought self-testing would eliminate logistical and reduce psychological CC screening barriers. Findings provide insights into facilitators and barriers of completing an HPV self-test at home, returning it, reporting results, and providing needed follow-up care. To the authors' knowledge, no systematic research exists addressing providers' views regarding women's use of HPV self-tests and the relation of such use to fostering subsequent Pap testing. This information will be useful in developing CC screening programs that include mailed HPV self-tests, as well as encouragement of follow-up Pap testing to meet existing CC screening guidelines.